L’avenir de l’assurance : modèle alpin ou modèle maritime ? - Albert, Michel (Assurances)

(untitled) (HEC Montréal, 1991)
Michel Albert, President of A.G.F., presents a very interesting reflection on the economic role of insurance and how its development parallels the origin and rise of capitalism. The author basically discusses two very different models of capitalism: the rhenan model and the American model, each of which is illustrated from two distinct insurance perspectives: marine and alpine. The conclusion focuses on the future of insurance by creating new opportunities for consumer needs.